"Dodobra me je očaralo" - Wilders, Marline Lisette (Amfiteater (Ljubljana), 2015)
This article investigates the similarities and differences on how spectators experience theatre performances grouped along large, transnationally present types as Spoken Theatre, Dance Theatre, Musical Theatre and Kleinkunst. Our findings are based on the analysis of the extensive data collected by the Project on European Theatre Systems (STEP) through a quantitative and qualitative audience research between 2010-2014 in Groningen (NL), Tartu (EE), Debrecen (HU) and Tyneside (UK). The results portray a generally very satisfied audience with small but significant differences between the types and the cities. The analysis is carried out along two interconnected tracks: dimensions of theatrical experience, based on a revised version of Van Maanen's TEAM model, are compared to clusters of keywords, which emphasise certain aspects of spectators' experience. The research manages to highlight specific patterns of theatre reception that fuel an exciting discussion on how to interpret certain key components of theatre experiences: immersion, personal and social relevance, cognitive and emotional engagement, complexity.
Keywords: Europe; Evropa; experiential values; genres; gledališče; gledališka recepcija; gledališke izkušnje; gledališki žanri; international comparative theatre survey; mednarodne primerjave; občinstvo; STEP; theater; theatre reception; theatrical experience